134-156 Washington Street, ca. 1865-73 (Tufts Archival Research Center, 2005)
Elevated view northeast of (left to right) 134-156 Washington Street, located between Spring Lane to the north-northeast and Franklin Street to the south-southwest. Signage and awnings adorn several buildings lining the southeast side of Washington Street. The facade and steeple of the Old South Meeting House, located on Washington Street at the northeast corner of Washington and Milk Streets, is included in the center of the carte-de-visite. Old South Meeting House built by Joshua Blanchard, 1729 3 1/2 x 2 1/4, 3 15/16 x 2 3/8 overall Cartes-de-visite